S Trimer Derived from SARS-CoV-2 B.1.351 and B.1.618 Induced Effective Immune Response against Multiple SARS-CoV-2 Variants - Hongye Wang; Zengshuai Wang; Liang Ma; Xiaoyong Zhu; Bingxiang Li; Yuhang Huang; Jingwen Li; Ming Sun; Li Shi; Yufeng Yao (Vaccines, 2023)
The spread of SARS-CoV-2 and its variants leads to a heavy burden on healthcare and the global economy, highlighting the need for developing vaccines that induce broad immunity against coronavirus. Here, we explored the immunogenicity of monovalent or bivalent spike (S) trimer subunit vaccines derived from SARS-CoV-2 B.1.351 (S1-2P) or/and B.1. 618 (S2-2P) in Balb/c mice. Both S1-2P and S2-2P elicited anti-spike antibody responses, and alum adjuvant induced higher levels of antibodies than Addavax adjuvant. The dose responses of the vaccines on immunogenicity were evaluated in vivo. A low dose of 5 μg monovalent recombinant protein or 2.5 μg bivalent vaccine triggered high-titer antibodies that showed cross-activity to Beta, Delta, and Gamma RBD in mice. The third immunization dose could boost (1.1 to 40.6 times) high levels of cross-binding antibodies and elicit high titers of neutralizing antibodies (64 to 1024) prototype, Beta, Delta, and Omicron variants. Furthermore, the vaccines were able to provoke a Th1-biased cellular immune response. Significantly, at the same antigen dose, S1-2P immune sera induced stronger broadly neutralizing antibodies against prototype, Beta, Delta, and Omicron variants compared to that induced by S2-2P. At the same time, the low dose of bivalent vaccine containing S2-2P and S1-2P (2.5 μg for each antigen) significantly improved the cross-neutralizing antibody responses. In conclusion, our results showed that monovalent S1-2P subunit vaccine or bivalent vaccine (S1-2P and S2-2P) induced potent humoral and cellular responses against multiple SARS-CoV-2 variants and provided valuable information for the development of recombinant protein-based SARS-CoV-2 vaccines that protect against emerging SARS-CoV-2 variants.